2016
DOI: 10.1177/0271678x16641129
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the changes in oxygen extraction fraction and cerebral activity caused by caffeine and acetazolamide

Abstract: A quantitative estimate of cerebral blood oxygen saturation is of critical importance in the investigation of cerebrovascular disease. We aimed to measure the change in venous oxygen saturation (Y) before and after the intake of the vaso-dynamic agents caffeine and acetazolamide with high spatial resolution using susceptibility mapping. Caffeine and acetazolamide were administered on separate days to five healthy volunteers to measure the change in oxygen extraction fraction. The internal streaking artifacts i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 78 publications
2
37
0
Order By: Relevance
“…gray matter), while the opposite was found in the white matter and lower part of the brain. Our results are consistent with previous ASL findings, which reported that decreasing CBF were widespread in the grey matter after caffeine intake (Buch et al 2017; Merola et al 2017). Compared to the delay map difference shown in Figure 5.a, we found that the regions of vessel constriction after caffeine intake overlap largely with the regions where the blood flow speed increases.…”
Section: Discussionsupporting
confidence: 93%
“…gray matter), while the opposite was found in the white matter and lower part of the brain. Our results are consistent with previous ASL findings, which reported that decreasing CBF were widespread in the grey matter after caffeine intake (Buch et al 2017; Merola et al 2017). Compared to the delay map difference shown in Figure 5.a, we found that the regions of vessel constriction after caffeine intake overlap largely with the regions where the blood flow speed increases.…”
Section: Discussionsupporting
confidence: 93%
“…even calibrated BOLD [2][3][4] and many longitudinal FMRI studies have used ASL acquisitions (for examples, see refs [5][6][7][8] ).…”
Section: Magnetic Resonance In Medicinementioning
confidence: 99%
“…aging ( Acosta-Cabronero et al., 2016 ; Betts et al., 2016 ; Darki et al., 2016 ; Li et al., 2014 ; Persson et al., 2015 ), drug addiction ( Ersche et al., 2017 ), Alzheimer's disease ( Acosta-Cabronero et al., 2013 ; Ayton et al., 2017 ; Moon et al., 2016 ; van Bergen et al., 2016b ), Parkinson's disease ( Acosta-Cabronero et al., 2017 ; Guan et al., 2017 ; He et al., 2015 ), Huntington's disease ( Dominguez et al., 2016 ; van Bergen et al., 2016a ), neurodegeneration with brain iron accumulation ( Lobel et al., 2014 ), neuromuscular disease ( Acosta-Cabronero et al., In Press ; Costagli et al., 2016 ; Schweitzer et al., 2015 ), demyelinating disease ( Bian et al., 2016 ; Chen et al., 2014 ; Cronin et al., 2016 ; Li et al., 2016 ; Wisnieff et al., 2015 ; Zhang et al., 2016 ) and traumatic brain injury ( Liu et al., 2016 ). QSM has also been proposed for vascular monitoring both at single time points ( Fan et al., 2015 , 2016 ; Ozbay et al., 2015 ) or in combination with the MRI technique of arterial spin labelling to infer cerebral metabolic rates of oxygen extraction ( Buch et al., 2017 ; Zhang et al., 2018 ); and dynamically, using fast echo-planar acquisitions for functional MRI (fMRI) applications ( Balla et al., 2014 ; Bianciardi et al., 2014 ; Chen and Calhoun, 2015 ; Ozbay et al., 2016 ; Sun et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%